Welcome to Dog Beach - Greenwald, Lisa (Greenwald, Lisa. Seagate summers series, 2015)
Twelve-year-old Remy loves the traditions of Seagate, the island where her family spends every summer vacation, but after her grandmother and a special dog die, and her relationship with best friends Bennett and Micayla changes, Remy takes comfort in the company of the Dog Beach--where she hatches a plan to bring her friends closer and recapture the Seagate magic.